Perspective of Maternal Deaths: A Retrospective Autopsy Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
Reducing maternal mortality has been a constant struggle globally. The major causes of maternal mortalityremain to be ante and post-partum haemorrhage, anaemia, obstructed labour, hypertensive disorders andpost-partum infections, liver disorders as observed in various studies. The present study was carried outwith view to determine factors causing maternal deaths, and utility of autopsy with autopsy record as auseful and adjunct data source for ascertainment of maternal deaths. In this study we have retrospectivelyconsidered the autopsy of maternal cases during 2015 to 2019 referred to RCSM GMC Kolhapur, Kolhapur,Maharashtra. Of the total 66 cases of maternal deaths, maximum number of cases were seen in age groupof 20 to 29 years comprising 42 out of 66 (63.63%), Maximum cases 53 (81.30%) were resident of ruralareas. Maximum causes of death on autopsy were direct causes, of which hemorrhage was the predominantcause. Most of the cases (42 out of 66 ) died within 24 hours of admission to the hospital. The determinantsof maternal mortality need to be studied through the lens of autopsy.